Tourism management: analysis, behaviour and strategy - Woodside, A. G.; Martin, D.; Martin, D.; Woodside, A. G. (Wallingford :CAB International, 2008)
This book provides in-depth empirical reports on specific topics within five general areas of tourism management and marketing: (1) scanning and sense making; (2) planning; (3) implementing; (4) evaluating actions/process and performance outcomes; and (5) administering. Offering descriptions, tools and examples of tourism management decision making, the book is useful for students in tourism and management and for tourism executives. It has 27 chapters and a subject index.
Keywords: EE119 - Leisure, Recreation and Tourism Economics, (New March 2000); EE700 - Marketing and Distribution; UU700 - Tourism and Travel